The University of Pennsylvania Medical School Commencement of 1889: Aequanimitas and the Agnew Clinic. Issue 6 (December 2021) - Kaiser, Larry R.; Morris, Jon B.
Abstract : N/A: Academic commencements ceremonies usually do not result in memorable occasions and once ended usually are forgotten. Not so for the University of Pennsylvania's School of Medicine commencement on May 1, 1889, which was marked by an address by William Osler, the retirement of the renowned Professor of Surgery, D. Hayes Agnew, and the presentation to the University of Thomas Eakins' remarkable masterpiece, "The Agnew Clinic." Osler had been on the faculty of the University for 5 years and in his keynote address, Aequanimitas, he laid out 2 elements, imperturbability and equanimity, that he stated would "make or mar" the lives of the students he was addressing. His words and message that day have continued to resonate for medical students and many others up to the present day. Osler ended his address on a more somber note, seemingly surprising the assembled, by announcing his imminent departure from the University. He would soon be one of the 4 founders of the Johns Hopkins Hospital along with fellow Penn faculty member, Howard Kelly. Osler was not the only one on the verge of leaving as this commencement also marked the end of the career of D. Hayes Agnew. To honor him on this occasion of his retirement the 3 classes of medical students had commissioned Eakins to paint a portrait of their revered professor, which was presented on this commencement day and accepted by Trustee Dr S. Weir Mitchell on behalf of the University. The day was indeed one to be remembered.